1995
DOI: 10.1038/eye.1995.102
|View full text |Cite
|
Sign up to set email alerts
|

Dislocated nuclear fragments after cataract surgery

Abstract: Posterior nuclear dislocation is a serious complication of cataract surgery, especially when using the phacoemulsification technique. So far, there have been only a few reports concerning the indications and timing of vitrectomy with nuclear removal as well as long-term visual outcome of these eyes. We analysed 23 consecutive patients (follow-up at least 3 months) with intravitreal nuclear remnants after cataract surgery treated with vitrectomy and removal of posteriorly dislocated nuclei. All the eyes had inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
3

Year Published

1998
1998
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 9 publications
2
31
3
Order By: Relevance
“…This percentage is apparently lower compared with other published series with 41-82% of cases achieving a final visual acuity of 6/12 or better, regardless of the time interval between cataract and vitreous surgery. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]24 This may be due to a large proportion (31%) of our cases having pre-existing ocular diseases before cataract surgery, with an overall median preoperative visual acuity of 6/90. In the series by Kageyama et al, 5 the median preoperative visual acuity was 6/15 with only 12% of cases had pre-existing ocular comorbidity.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This percentage is apparently lower compared with other published series with 41-82% of cases achieving a final visual acuity of 6/12 or better, regardless of the time interval between cataract and vitreous surgery. [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]24 This may be due to a large proportion (31%) of our cases having pre-existing ocular diseases before cataract surgery, with an overall median preoperative visual acuity of 6/90. In the series by Kageyama et al, 5 the median preoperative visual acuity was 6/15 with only 12% of cases had pre-existing ocular comorbidity.…”
Section: Discussionmentioning
confidence: 93%
“…Kim et al 8 reported that 75% of eight eyes operated on the same day as the cataract surgery had final vision of 6/9 or better, while only 63% of the other 54 eyes operated later had final vision of 6/12 or better. Tommila and Immonen 17 reported that of eyes undergoing vitrectomy immediately after cataract extraction 57% of seven eyes achieved a vision of 6/12 or better, compared with 78% of 16 eyes that were vitrectomised 1-7 days after cataract surgery. Terasaki et al 18 reported that 75% of four eyes operated on the same day as the cataract surgery had final vision of 6/9 or better, compared with 70% of the other 10 eyes operated 2-7 days after cataract surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In these reports no relationship was found between visual acuity or the development of chronic glaucoma and the timing of vitrectomy. However, some recent reports suggest that vitrectomy within a week is advantageous in reducing a number of complications (Tommila & Immonen 1995;Yeo et al 1999). A possible bias in retrospective studies on retained lens fragments may be a tendency to operate earlier the more severe the complications are.…”
Section: Discussionmentioning
confidence: 99%